2020
DOI: 10.1038/s41598-020-60318-6
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel, chronic widespread pain, chronic fatigue and related syndromes are prevalent and highly overlapping in the general population: DanFunD

Abstract: prevalence of functional somatic syndromes (fSS) in the general population varies with observed overlap between syndromes. However, studies including a range of fSS are sparse. We investigated prevalence and characteristics of various fSS and the unifying diagnostic construct bodily distress syndrome (BDS), and identified mutual overlap of the FSS and their overlap with BDS. We included a stratified subsample of 1590 adults from a randomly selected Danish general population sample (n = 7493). Telephonic diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 90 publications
3
69
0
2
Order By: Relevance
“…The trends outlined in our study closely mirror a number of previous reports on the experiences of patients suffering from other, in large part, medically unexplained syndromes associated with chronic fatigue (Bennett et al, 2007;Kanaan et al, 2007;de Lourdes Drachler et al, 2009;McBeth et al, 2015;Rosendal et al, 2017;Petersen et al, 2020). These phenomenological similarities could result for a few different reasons:…”
Section: Future Directionssupporting
confidence: 86%
“…The trends outlined in our study closely mirror a number of previous reports on the experiences of patients suffering from other, in large part, medically unexplained syndromes associated with chronic fatigue (Bennett et al, 2007;Kanaan et al, 2007;de Lourdes Drachler et al, 2009;McBeth et al, 2015;Rosendal et al, 2017;Petersen et al, 2020). These phenomenological similarities could result for a few different reasons:…”
Section: Future Directionssupporting
confidence: 86%
“…In fact, there appears to be a consistent overlap between fatigue, pain, depression, and anxiety. [ 24 , 25 ] Our focus is not on making the presence of fatigue sufficiently distinctive from other symptoms, rather, preventing it from a vicious circle of mutual influence.…”
Section: Discussionmentioning
confidence: 99%
“…A register-based study by Petersen and colleagues found a high burden of physical comorbidity among FSS patients as compared with control patients 27 . Physician-led telephone interviews among participants of the Danish Study of Functional Disorders (DanFunD) found high overlap between five different FSS disorders, observing 20 out of 26 possible combinations 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we are unable to differentiate between a patient in remission and a patient who chooses no longer to consult for a persisting FSS. The data therefore provide the perspective of the ambulatory physicians, which is necessarily different from that provided by an epidemiological cohort such as the DanFunD study 28 .…”
Section: Strengths and Limitationsmentioning
confidence: 94%